Janus medical sponge dressings with anisotropic wettability for wound healing. (June 2021) - Zhang, Han; Chen, Canwen; Zhang, Hui; Chen, Guopu; Wang, Yuetong; Zhao, Yuanjin
Highlights: Preparation of superhydrophilic porous PU sponge by plasma. Stability of the surface of sponge sprayed with PDA-coated SiO2 nanoparticles. PFDTES vapor deposition for the generation of superhydrophobic surface. Sufficient drainage force from superhydrophilic part to transport liquid. Unidirectional transport of liquid without wetting superhydrophobic surface. Abstract: Excessive exudates around the wound often lead to severe infections and prolonged nonhealing of the wound, and various dressings have been studied to solve this medical problem. Herein, we present novel Janus polyurethane (PU) sponge dressings with anisotropic surface wettability and unidirectional liquid transportation capability for wound healing. The specific wettability dressings were fabricated by immobilized superhydrophobic silica (SiO2 ) nanoparticles onto one surface of the superhydrophilic PU sponges with the assistance of polydopamine (PDA). Due to the draining force provided by the superhydrophilic part, the liquid could be transported unidirectionally through the superhydrophobic surface without wetting it. Based on this advantage, it was demonstrated that the Janus PU sponges could act as biomedical dressings to solve the problem of excessive wetting between the dressing and the wound, reduce the risk of infection, and accelerate the efficiency of the wound healing process. Thus, we believe that the novel Janus dressing is ideal for the management of excessive exudates around the wound and highly desirable for clinical applications. Graphical abstract: Janus PU sponge dressings with anisotropic wettability propose a new drainage plan. The superhydrophilic part of them provides a sufficient drainage force to transport liquid through its superhydrophobic surface without wetting it, which indicates that the novel dressings can keep the wound relatively dry so as to accelerate the wound healing process. Image, graphical abstract